Do Creditor Rights Increase Employment Risk? Evidence from Loan Covenants. (December 2016) - FALATO, ANTONIO; LIANG, NELLIE
ABSTRACT: Using a regression discontinuity design, we provide evidence that there are sharp and substantial employment cuts following loan covenant violations, when creditors gain rights to accelerate, restructure, or terminate a loan. The cuts are larger at firms with higher financing frictions and with weaker employee bargaining power, and during industry and macroeconomic downturns, when employees have fewer job opportunities. Union elections that create new labor bargaining units lead to higher loan spreads, consistent with creditors requiring compensation when employees gain bargaining power. Overall, binding financial contracts have a large impact on employees and are an amplification mechanism of economic downturns.